(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Time lag is a sliding body that undergoes the process of crushing chains and crushing , in other colas it is a multi-layered galaxy that grinds its teeth with anger and rage. NPZHB - complex and coordinated, according to the description of movements, the hinges are locking [1.3.5]. Other authors [2.4.6.8] believe that the superficial area of the flange of the Chin lower jaw exhibits a saddle joint, the surface of which is similar to the surface of the wristtoe core joints of the big toe. From a biomechanical point of view, the junction of the lower jaw (p / j) with the skull consists of four synergistic moving joints, so some authors propose to call the CHIN LOWER JAW “Chin lower jawcomplex”. According to the author (Yu. Simanovskoy) [7.9.10], Chin lower jaw is a complex musculoskeletal carcass with many components, involved in the connection of the upper jaw (y / j) and the rows of teeth of the p / j, providing the movement of the p / j in different directions. block. Motions are an example of motion around instantaneous and variable axes, which is a condition in biomechanics. The authors (O.G. Bugrovetskaya and Hammual [11.13.15.16] divide the network of types of motion around different axes as follows; a horizontal arrow involved in the opening and closing of the mouth and between the arrows; slip planes lying at the level of the p / j tongue and varying in p / j protrusion and retrusion; a side-sliding bullet at the end of the bullet; the whole p / j slides and moves laterally; axis of rotation around the vertical, located in the center of the right or left joint; a curved axis located at the center of one or the other joint for the combined movements of deviation and opening of the mouth.